Analisis Dampak Kesehatan Masyarakat Terhadap Pembangunan Ekonomi: Studi Kasus Kotabumi - Hasan, Saukani; Rumianti, Susti; Mervita, Eda (Jurnal Ilmiah Manajemen Kesatuan, 2022)
Public health is a vital resource for the growth and life of a nation. One effort to improve health degrees is to improve environmental health. Environmental health is an important factor in social life, even being a determinant of the welfare of the population. Health is one of the essential human resources needed to sustain economic development. This is because health is a prerequisite to increasing productivity, so health and economics have a powerful influence on one another. Health affects the economy, with high public health levels, the productivity of human labor is also high. When comparing the welfare rates of various community groups, it is important to look at life expectancy and annual income levels. In countries with better health rates, the average live longer, which means they have a financial opportunity to earn more. According to kotabumi's rate of life expectancy and public health, it is concluded that the region's health status still requires special attention. Keywords : Health, Ecomomics, and Life Expectancy